Formulation and Evaluation of Peel-Off Gel Mask with Tomato Fruit Extract Using PVA Base - Rahmi, Ai; Yusuf, Anna L (LPPM STIKes Muhammadiyah Ciamis, 2024)
Tomatoes have been widely used in society as a homemade mask by mashing them until smooth and then applying them to the face. Tomatoes have health and beauty benefits because they have high nutritional content such as antioxidants lycopene, vitamin C, potassium, folate and vitamin A. Using tomatoes as a mask has benefits for the skin because they have antioxidant activity so they can provide a brightening effect and can prevent aging. Peel-off gel masks are one of the masks that are practical to use, because after drying the mask can be removed immediately without rinsing. Peel-off gel masks are made with a Polyvinyl Alcohol (PVA) base as a gelling agent that has the ability to form a film layer so that it is easy to peel off after drying. Evaluation of the peel-off gel mask preparation consists of organoleptic tests, viscosity tests, pH tests, spreadability tests and drying time tests. From the results of organoleptic observations, the resulting preparation is a thick preparation with a distinctive tomato odor and has a brick red color. The evaluation results of the viscosity test, pH test, spreadability test and drying time test showed that the peel-off gel mask preparation met the requirements.